Reduction of COD and Highly Coloured Mature Landfill Leachate by Tin Tetrachloride with Rubber Seed and Polyacrylamide - Siti Fatihah Ramli (MDPI AG, 2021)
Tin tetrachloride (SnCl4) as a coagulant and rubber seed (Hevea brasiliensis) (RS), and polyacrylamide (PAM) as the coagulant aid were investigated in this work to treat matured and stabilised landfill leachate rich in COD and colour. A standard jar test was conducted at different pH values and dosages of coagulant/coagulant aid. When SnCl4 acted as the primary coagulant, the optimum conditions occurred at pH 8 and 10,000 mg/L dosages, with 97.3% and 81% reductions of colour and COD, respectively. Both RS and PAM were not effective when used alone. When RS was used as the coagulant aid, the dosage of SnCl4 was reduced to 8000 mg/L. The colour reduction was maintained at 97.6%, but the COD removal dropped to 43.1%. In comparison, when PAM was supplemented into 6000 mg/L SnCl4, the reduction in colour was maintained at 97.6%, and the COD removal was almost at par when SnCl4 was used alone. The addition of polymers as the coagulant aid helped in improving the sludge properties with a better settling rate (SSR) and larger flocs size. The decline of the SVI value indicates that less amount of sludge will be disposed of after the treatment. In addition, the rise of settling velocity (SSR) will reduce the size of the settling tank used in coagulation-flocculation treatment. Based on the results, it can be concluded that incorporation of coagulant aid into the treatment reduced the primary coagulant dosage without affecting the removal performances of pollutants.